2016
DOI: 10.1016/j.prostaglandins.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fat diet on plasma profiles of eicosanoid metabolites in mice

Abstract: Obesity is a serious health problem in the US and is associated with increased risks of various human diseases. To date, the mechanisms by which obesity increases the risks of a wide range of human diseases are not well understood. Here we used a LC–MS/MS-based lipidomics, which can analyze >100 bioactive lipid mediators produced by cyclooxygenase, lipoxygenase, and cytochrome P450 enzymes, to analyze plasma profiles of lipid mediators in high-fat diet induced obesity in C57BL/6 mice. Our results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In addition, adverse effects as result of high-fat exposure were reported in the following areas: brain, cognition, memory, mental well-being, Alzheimer’s, autistic behaviour [ 33 , 34 , 61 63 ]; obesity, metabolic dysfunction, inflammation, liver damage, cardiometabolic risks’ [ 34 , 38 , 64 68 ]; risks of cancer [ 66 , 69 ]; osteoporosis [ 70 ]. In elegant animal models, Cani et al [ 71 ] clearly demonstrated that high fat feeding, which induces low intakes of fermentable dietary fibers, may lead to intestinal microbiota changes which are associated with an increased intestinal permeability resulting in endotoxemia and triggers for inflammation and metabolic disorders (note: the examples are only given as an illustration, not for an exhaustive picture).…”
Section: Is a Lchf Diet Healthy And Safe?mentioning
confidence: 99%
“…In addition, adverse effects as result of high-fat exposure were reported in the following areas: brain, cognition, memory, mental well-being, Alzheimer’s, autistic behaviour [ 33 , 34 , 61 63 ]; obesity, metabolic dysfunction, inflammation, liver damage, cardiometabolic risks’ [ 34 , 38 , 64 68 ]; risks of cancer [ 66 , 69 ]; osteoporosis [ 70 ]. In elegant animal models, Cani et al [ 71 ] clearly demonstrated that high fat feeding, which induces low intakes of fermentable dietary fibers, may lead to intestinal microbiota changes which are associated with an increased intestinal permeability resulting in endotoxemia and triggers for inflammation and metabolic disorders (note: the examples are only given as an illustration, not for an exhaustive picture).…”
Section: Is a Lchf Diet Healthy And Safe?mentioning
confidence: 99%
“…As a result, C18-derived oxylipins are present in much higher amounts than would be predicted from their fatty acid levels, suggesting that they may have a greater impact on physiology. Although much less is known about the physiological effects of C18 compared with C20-and C22-derived oxylipins, they have been associated with varied effects that are either protective or harmful in a number of states, including inflammation in processes associated with atherosclerosis, mitogenic effects associated with cancer, pain sensitivity, and with obesity and the metabolic syndrome (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic low-grade inflammation was reported to play a pivotal role in the pathogenesis of obesity ( Hotamisligil, 2006 ). Thus, targeting inflammation appears as an attractive strategy to counter the burden of obesity and its associated comorbidities ( Hardwick et al, 2013 ; Wang et al, 2016 ). Among potential targets, PGE2 appears of particular interest since previous works have reported their contribution to the uncontrolled inflammation observed in obese individuals ( González-Périz and Clària, 2010 ).…”
Section: Discussionmentioning
confidence: 99%